Experimental study on bubble dynamics and wall heat transfer arising from a single nucleation site at subcooled flow boiling conditions – Part 1: Experimental methods and data quality verification. (September 2016) - Yoo, Junsoo; Estrada-Perez, Carlos E.; Hassan, Yassin A.
Highlights: A subcooled flow boiling experiment is performed with a single nucleation site approach. An image acquisition/analysis strategy for reliable measurement of boiling parameters is discussed. A repeatability and thus reliability of statistics obtained from the present data acquisition method is discussed. Major sources of uncertainty and uncertainty quantification processes are described. Abstract: A novel experimental method and data acquisition/analysis strategy that ensures reliable measurements of various subcooled flow boiling parameters is discussed. In this study, all experiments were performed by keeping a single active nucleation site within the entire heated area in a square upward flow channel. This approach greatly facilitated the observation of bubble and wall heat transfer features in subcooled boiling flow. Vapor bubbles originating from the nucleation site were observed with both micro- and macroscopic views from high-speed cameras while corresponding wall temperature was measured by an infrared camera. This allowed simultaneously capturing various bubbles characteristics with multiple scales (both space and time) as well as their impact on wall heat transfer. In addition, efforts were made to characterize the observed boiling behavior with high statistical accuracy by analyzing numerous images taken at each test condition. This study proves that by taking the current strategy excellent repeatability and thus reliability can be achieved for a wide range of flow boiling parameters such as bubble size, bubble velocity, statistical distribution of bubble size and time-averaged wall heat transfer coefficients. Also, the major sources of uncertainty for each measurement are thoroughly investigated, from which the final uncertainties are determined. Overall, the present study suggests what we must concern to achieve truly reliable and useful data from any boiling experiments.